Spaceborne Microwave Remote Sensing of Arctic Sea Ice During Spring - Drobot, Sheldon D.; Anderson, Mark R. (DigitalCommons@University of Nebraska - Lincoln, 2000)
This paper outlines the fundamental roles sea ice plays during the spring Arctic climate, and it demonstrates the use of passive microwave remote sensing in measuring climatically important sea ice variables during the spring transitional period. It discusses the theoretical concepts underlying passive microwave remote sensing of sea ice, and it summarizes the historical use of satellite microwave radiometry in the Arctic region. In addition, this paper discusses the derivation of climatically important sea ice variables, including sea ice extent, concentration, multiyear ice fraction, and snow melt onset, with additional comments on the precision and accuracy of the remote sensing estimates. It also discusses interannual trends in sea ice extent and presents interannual trends in snow melt onset dates. Finally, this paper provides a brief discussion on the future directions in passive microwave remote sensing of climatically important sea ice variables during the spring transitional period.